The Show Must Go On II: Statistics In (Engineering) Higher Education - Nascimento Maria M.; Morais Eva (De Gruyter, 2020)
The COVID-19 pandemic forced Portuguese higher education institutions to go home and teach online. Therefore, we had an online experience teaching the Statistics course to the Social Service degree. Viewing this school year experience, we decided to make some changes in the Statistical courses of Informatics, Mechanical and Civil Engineering degrees. Our main concern is still the uncertainty of what is yet to come in the next first semester: face-to face or emergency remote education. In this work we present our ideas in order to develop our students' skills - collaboration, communication, citizenship/culture, creativity, and critical thinking - through their probability and statistics course and as part of their degree's curricula.